Elaboração e validação de um instrumento para avaliação da raiva em relacionamentos amorosos - Barbosa, Thamires Pereira (2023)
Violence against women perpetuated by intimate partners is currently a phenomenon that occurs worldwide and has concentrated a large number of investigations with the aim of assisting in prevention and intervention actions. It is known that the causes of violence are multifactorial and complex, and include factors external and internal to individuals, with some of the emotional and cognitive processes interfering in the manifestation of aggression. On the national scene, barnacles are also a discreet literature that concerns the understanding of emotional mediators as predictors of aggression. From this point of view, the main objective of this study is to create a life support measure related to romantic conflict situations. After semantic validation of the scale, the parameters of the psychometric properties are tested using factor analysis, Cronbach's alpha coefficients and analyzes via Item Response Theory (IRT). The results confirm the psychometric adequacy of the measure, suggesting a three-dimensional solution with high loadings without a general factor and high internal consistency, but a brief version of the scale with a monophasic solution was also developed. It is proven that the intended objective was satisfied, so that, at the end of the investigation, there is a valid and reliable measure that can be used, both for tracking and for investigation, to understand and validate the manifestation of anger in romantic conflicts. The instruments resulting from this study, as well as others, can help to understand the factors related to the manifestation of violence in romantic relationships.